2018
DOI: 10.1016/j.ijscr.2018.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Unusual case of intraluminal cecal recurrence of a low grade appendiceal mucinous neoplasm (LAMN)—Case report and brief literature review

Abstract: HighlightsPenetration of the visceral peritoneum by a mucinous neoplasm consists the cardinal point in the management and prognosis.Patients with LAMN confined to the muscularis propria after histologic examination of the entire appendix (pTis) have essentially no risk of recurrence.There are no clear guidelines regarding appropriate management of appendiceal LAMNs with positive margins, especially when confined within the serosa.A simple cecectomy is traditionally suggested by some authors, but according to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The surgical margins were negative and we considered not to perform a right hemicolectomy. In the LAMN cases where the tumor is localized, many publications are agreed that simple appendectomy is sufficient to be curative [ 2 , 5 , [9] , [10] , [11] ], but there are still no guidelines about the appropriate management when the surgical specimen has positive surgical margins [ 2 , 3 , 12 ]. During our review we found a case report of Givalos, N. et al affirming that there are reports of experts suggesting a cecectomy in mucinous neoplasms with positive margins with negative lymph nodes [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The surgical margins were negative and we considered not to perform a right hemicolectomy. In the LAMN cases where the tumor is localized, many publications are agreed that simple appendectomy is sufficient to be curative [ 2 , 5 , [9] , [10] , [11] ], but there are still no guidelines about the appropriate management when the surgical specimen has positive surgical margins [ 2 , 3 , 12 ]. During our review we found a case report of Givalos, N. et al affirming that there are reports of experts suggesting a cecectomy in mucinous neoplasms with positive margins with negative lymph nodes [ 12 ].…”
Section: Discussionmentioning
confidence: 99%